2010
DOI: 10.1002/jbm.a.32700
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the binding of Cr(III) complexes to bovine and human serum proteins: A proteomic approach

Abstract: Chromium (Cr) compounds are widely used in alloys manufacturing and forming processes. One of the main concerns in the use of cobalt-chromium (Co-Cr) alloy-based implants is the long-term fate of Co and Cr ions in the blood, organs, and urine of patients. Our previous studies have shown that Cr(III) forms complexes in different cell culture media, whereas Cr(VI) does not form any detectable structure under the same conditions. Because Cr(VI) is known to be more toxic than Cr(III), we hypothesized that the pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
25
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 62 publications
4
25
0
Order By: Relevance
“…The measurements were performed with a significantly shorter equilibrium time after the addition of Cr(III), only 5 s compared with 300 s [for Cr(VI)], due to a decreasing signal of Cr(III) with time [41]. Even though these findings imply similar results independent of chromium speciation in the case of BSM, the situation may be different for LYS, HSA, and/or BSA (not investigated in this study) as suggested by Tkaczyk et al for BSA [3]. The approach of this study should at this stage hence be only applied for the methodology adding Cr(VI).…”
Section: Chromium-protein Complexation-influence Of Protein Type and supporting
confidence: 49%
See 1 more Smart Citation
“…The measurements were performed with a significantly shorter equilibrium time after the addition of Cr(III), only 5 s compared with 300 s [for Cr(VI)], due to a decreasing signal of Cr(III) with time [41]. Even though these findings imply similar results independent of chromium speciation in the case of BSM, the situation may be different for LYS, HSA, and/or BSA (not investigated in this study) as suggested by Tkaczyk et al for BSA [3]. The approach of this study should at this stage hence be only applied for the methodology adding Cr(VI).…”
Section: Chromium-protein Complexation-influence Of Protein Type and supporting
confidence: 49%
“…Studies on chromium complexation and reported stability constants of different organic-chromium complexes are scarce in the literature. However, it has been shown that Cr(III) forms complexes with different organic species, including amino acids [2], bovine serum albumin (BSA) [3], other proteins, and DNA [4]. It has furthermore been shown that mainly trivalent chromium binds to proteins and DNA [4] even if hexavalent chromium is added, with tyrosine and cysteine, followed by histidine, methionine, and threonine as major binding sites for chromium to proteins [4].…”
Section: Introductionmentioning
confidence: 99%
“…It has been previously reported that Cr interacts with different serum proteins including hemoglobin, transferrin, and albumin58. Co has been proposed to bind to several proteins involved in the cellular redox system and ROS clearance59.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanisms and causes of this hypersensitivity remain largely unknown. They may be due to metal degradation products that can complex with serum proteins [1][2][3] to form haptens 62 , to which individuals may have a different response threshold 63 . It is also possible that proteins complexed with the particles detaching from the tribolayers, as described earlier, form haptens, especially considering that these proteins are likely denatured from exposure to high shear rates and elevated temperatures.…”
Section: Biological Effectsmentioning
confidence: 99%
“…Progress has been largely based on empirical information, and the underlying wear mechanisms are not well understood. The release of metal ions, which can complex with proteins [1][2][3] , and the formation of nanometer-sized wear particles [4][5][6] have raised concerns regarding metal hypersensitivity and potential genotoxicity.…”
mentioning
confidence: 99%